Dramatic Effects of 2-Bromo-5,6-Dichloro-1-β-d-Ribofuranosyl Benzimidazole Riboside on the Genome Structure, Packaging, and Egress of Guinea Pig Cytomegalovirus - Nixon, Daniel E. (American Society for Microbiology, 2004)
The halogenated benzimidazoles BDCRB (2-bromo-5,6-dichloro-1-β-d-riborfuranosyl benzimidazole riboside) and TCRB (2,5,6-trichloro-1-β-d-riborfuranosyl benzimidazole riboside) were the first compounds shown to inhibit cleavage and packaging of herpesvirus genomes. Both inhibit the formation of unit length human cytomegalovirus (HCMV) genomes by a poorly understood mechanism (M. R. Underwood et al., J. Virol. 72:717-715, 1998; P. M. Krosky et al., J. Virol. 72:4721-4728, 1998). Because the simple genome structure of guinea pig cytomegalovirus (GPCMV) provides a useful model for the study of herpesvirus DNA packaging, we investigated the effects of BDCRB on GPCMV. GPCMV proved to be sensitive to BDCRB (50% inhibitory concentration = 4.7 μM), although somewhat less so than HCMV. In striking contrast to HCMV, however, a dose of BDCRB sufficient to reduce GPCMV titers by 3 logs (50 μM) had no effect on the quantity of GPCMV genomic DNA that was formed in infected cells. Electron microscopy revealed that this DNA was in fact packaged within intranuclear capsids, but these capsids failed to egress from the nucleus and failed to protect the DNA from nuclease digestion. The terminal structure of genomes formed in the presence of BDCRB was also altered. Genomes with ends lacking a terminal repeat at the right end, which normally exist in an equimolar ratio with those having one copy of the repeat at the right end, were selectively eliminated by BDCRB treatment. At the left end, BDCRB treatment appeared to induce heterogeneous truncations such that 2.7 to 4.9 kb of left-end-terminal sequences were missing. These findings suggest that BDCRB induces premature cleavage events that result in truncated genomes packaged within capsids that are permeable to nuclease. Based on these and other observations, we propose a model for duplication of herpesvirus terminal repeats during the cleavage and packaging process that is similar to one proposed for bacteriophage T7 (Y. B. Chung, C. Nardone, and D. C. Hinkle, J. Mol. Biol. 216:939-948, 1990).